2009
DOI: 10.1111/j.1365-2591.2009.01642.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing in dental practice in Belgium

Abstract: Discrepancies between observed and recommended practice support the need for educational initiatives to promote rational use of antibiotics in dentistry in Belgium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
171
5
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(202 citation statements)
references
References 22 publications
20
171
5
6
Order By: Relevance
“…Su 24.421 pazienti visitati, a 1033 venne prescritto un antibiotico con una media, quindi, di 3 prescrizioni in due settimane. In particolare, vennero prescritti antibiotici a largo spettro (amoxicillina, amoxicillina+acido clavulanico e clindamicina) come unico trattamento, anche in assenza di coinvolgimento sistemico (febbre) e anche nel caso in cui la diagnosi fosse pulpite [7] . L'abuso di antibiotici da parte degli odontoiatri secondo gli autori contribuisce nettamente all'antibiotico resistenza [5][6][7] .…”
Section: Secondo Pipalova Et Al In Repubblicaunclassified
“…Su 24.421 pazienti visitati, a 1033 venne prescritto un antibiotico con una media, quindi, di 3 prescrizioni in due settimane. In particolare, vennero prescritti antibiotici a largo spettro (amoxicillina, amoxicillina+acido clavulanico e clindamicina) come unico trattamento, anche in assenza di coinvolgimento sistemico (febbre) e anche nel caso in cui la diagnosi fosse pulpite [7] . L'abuso di antibiotici da parte degli odontoiatri secondo gli autori contribuisce nettamente all'antibiotico resistenza [5][6][7] .…”
Section: Secondo Pipalova Et Al In Repubblicaunclassified
“…The most commonly used antibiotic in dental practice, for patients without any medical allergy, was found to be amoxicillin followed by metronidazole and amoxicillin with clavulanate [9][10][11][12][13]. While in patients with allergy to penicillin, choice of drug were: clindamycin [11], macrolides followed by clindamycin [12] and erythromycin [8].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the reason for consultation on the decision to prescribe antibiotics has already been evaluated. 16,17 Dailey and Martin 16 found that 62% of adult patients with pain and/or swelling did not receive any treatment; in another study, 18 59% of the patients with periapical abscesses were given antibiotics only, without any local treatment. If treatments were rendered to those patients, the number of inappropriate prescriptions in these studies could be lower.…”
Section: Discussionmentioning
confidence: 99%
“…Amoxicillin with or without clavulanic acid was the most administered antibiotic confi rming the results from other studies conducted in different countries. 7 -9 In contrast, narrow spectrum antibiotics were preferred in Norway 17 and North America. 22 Amoxicillin is the antibiotic of choice for the management of dental infections followed by amoxicillin in combination with clavulanic acid according to the current 6,22 recommendations.…”
mentioning
confidence: 99%
See 1 more Smart Citation